Manuel Álvarez Nazario, El arcaísmo vulgar en el español de Puerto Rico. Mayagüez, Puerto Rico, 1957; 219 pp. - Lope Blanch, Juan M. (El Colegio de México, 1958)
Se reseñó el libro: El arcaísmo vulgar en el español de Puerto Rico.